Aerodynamic characteristics of human movement behaviours in full-scale environment: Comparison of limbs pendulum and body motion. Issue 1 (February 2015) - Han, Z. Y.; Weng, W. G.; Huang, Q. Y.; Fu, M.; Yang, J.; Luo, N.
The aerodynamic effects of human movement can significantly influence the airflow motion and contaminants transmission in enclosed environments such as in aircraft cabins, cinema and conference room, and so it is necessary and important to study the characteristics of these aerodynamic effects. This work focuses on the aerodynamic characteristics of human movement behaviours including limbs pendulum and body motion. A thermal manikin is used in the corresponding environments to simulate these behaviours. The step frequencies of 20, 30, 40, 50 and 60 double steps per minute for limbs pendulum and the moving speeds of 0.5, 0.75, 1.0, 1.25 and 1.5 m/s for body motion are investigated in the experiments. In each case, the velocity distribution around the human body is measured by using hot-wire anemometers. The experimental results show that the characteristics of the velocity distribution induced by limbs pendulum depend on pendulum frequency and spatial location, and for body motion, it depends on moving speed, moving distance and spatial location. The analysis results show that body motion has a significant influence on the flow field, and its aerodynamic effects are greater than those due to limbs pendulum. When a human moves, more detailed profile of the human body leads to more complicated flow field in the nearby area.